Projecting the demand for economists in the Caribbean : the use of labour market signalling techniques - Downes, Andrew S. (1998)
Presents an overview of the methodologies for projecting the demand for economists. Assesses the demand for economists based on the use of labour market signalling techniques. Provides a few recommendations for assessing the demand for economists in the Caribbean in the twenty-first century.